2007
DOI: 10.1103/physrevc.75.044309
|View full text |Cite
|
Sign up to set email alerts
|

Deformation parameters and transition probabilities for shears bands in Pb isotopes

Abstract: Tilt angles, deformation parameters, angular momenta, and reduced magnetic dipole and electric quadrupole transition probabilities are calculated within the framework of the tilted-axis cranking model for shears bands in the neutron-deficient Pb isotopes 193 Pb to 202 Pb. The self-consistently calculated quadrupole-deformation parameters for the various configurations lie around ε 2 = −0.1, and the triaxiality is small. The tilt angle, i.e., the angle between the angular momentum and the nuclear symmetry axis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(54 citation statements)
references
References 29 publications
4
50
0
Order By: Relevance
“…In the left panel of Fig. 1, the calculated total angular momenta for one of the MR bands, Band 1, in 198 Pb as a function of the rotational frequency are shown in comparison with the data [30] and the PQTAC results [31]. It is found that both the tilted axis cranking CDFT and the PQTAC results agree well with the experimental data.…”
Section: Theoretical Frameworksupporting
confidence: 56%
“…In the left panel of Fig. 1, the calculated total angular momenta for one of the MR bands, Band 1, in 198 Pb as a function of the rotational frequency are shown in comparison with the data [30] and the PQTAC results [31]. It is found that both the tilted axis cranking CDFT and the PQTAC results agree well with the experimental data.…”
Section: Theoretical Frameworksupporting
confidence: 56%
“…Similar investigations along this line have been extended for three-dimensional cranking and the nuclear chirality is proposed [17]. Because of the high numerical complexity of the TAC model, even today most of the applications are based on simple phenomenological Hamiltonians, such as the pairing plus-quadrupole-quadrupole tilted-axis cranking (PQTAC) model [18]. Only recently nonrelativistic [19] and relativistic [20][21][22] codes have been developed for microscopic investigations of magnetic rotation in the framework of density functional theory.…”
Section: Introductionmentioning
confidence: 91%
“…The less satisfactory agreem ent for the highest observed spins can be due to a gradual shape change as recently observed in the 141 Nd isotope [6]. The calculated B(M 1) values decrease with increasing rotation frequency from 5 ^ for hw -0.1 to 3 n l for Hco = 0.6, indicating the presence o f the shears-bands m echanism [36].…”
Section: B the A / = 1 Band Interpreted By Tac Calculationsmentioning
confidence: 86%